2012
DOI: 10.1371/journal.pone.0029747
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome 2p14 Is Linked to Susceptibility to Leprosy

Abstract: BackgroundA genetic component to the etiology of leprosy is well recognized but the mechanism of inheritance and the genes involved are yet to be fully established.MethodologyA genome-wide single nucleotide polymorphism (SNP) based linkage analysis was carried out using 23 pedigrees, each with 3 to 7 family members affected by leprosy. Multipoint parametric and non-parametric linkage analyses were performed using MERLIN 1.1.1.Principal FindingsGenome-wide significant evidence for linkage was identified on chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…They suggested genomewide significant evidence for linkage on chromosome 2p14, and a suggestive evidence for linkage on chr.4q22 (rs1349350), chr.8q24 (rs1618523), and chr.16q24 (rs276990), as well as a moderate evidence for a linkage locus on chromosome 6q24–26 (rs6570858), overlapping a previously reported linkage region on chromosome 6q25-26 [112]. …”
Section: Genome-wide and Leprosysupporting
confidence: 51%
See 1 more Smart Citation
“…They suggested genomewide significant evidence for linkage on chromosome 2p14, and a suggestive evidence for linkage on chr.4q22 (rs1349350), chr.8q24 (rs1618523), and chr.16q24 (rs276990), as well as a moderate evidence for a linkage locus on chromosome 6q24–26 (rs6570858), overlapping a previously reported linkage region on chromosome 6q25-26 [112]. …”
Section: Genome-wide and Leprosysupporting
confidence: 51%
“…Recently, Yang et al [112] carried out a genome-wide single nucleotide polymorphism (SNP) based linkage analysis using 23 pedigrees, each with 3 to 7 family members affected by leprosy, in China [112]. They suggested genomewide significant evidence for linkage on chromosome 2p14, and a suggestive evidence for linkage on chr.4q22 (rs1349350), chr.8q24 (rs1618523), and chr.16q24 (rs276990), as well as a moderate evidence for a linkage locus on chromosome 6q24–26 (rs6570858), overlapping a previously reported linkage region on chromosome 6q25-26 [112].…”
Section: Genome-wide and Leprosymentioning
confidence: 99%
“…LL: LOD score (D20S889) = 1.36, p = 0.006. TT: LOD score (D20S835) = 0.74, p = 0.033 Wallace et al ( 2004 ) 185 extended families from Malawi (83 nuclear families in the discovery phase) 21q22 LOD score = 1.4, p ≈ 0.001 Yang et al ( 2012 ) 23 Chinese families, including 82 affected individuals 2p14 HLOD = 3.51 (REC), LOD score = 1.48, p = 0.005 4q22 HLOD = 2.92 (DOM), LOD score = 1.21, p = 0.009 8q24 HLOD = 2.74 (REC), LOD score = 1.22, p = 0.009 16q24 HLOD = 1.93 (DOM), LOD score = 1.37, p = 0.006 6q24-q26 LOD score = 1.54, p = 0.004 DOM dominant model; HLOD heterogeneity logarithm of odds; LOD logarithm of the odds; LL lepromatous leprosy; MB multibacillary leprosy; MLB maximum likelihood binomial; PB paucibacillary leprosy; REC Recessive model; TT tuberculoid leprosy a Follow-up association analysis of candidate genes located in the regions linked to the disease are not included in this table b For studies in which the population sample consists of an extension of a previous published GWLS, only the new findings from the extended population analysis are shown c Peak/maximum LOD score is shown for each locus when available d In multi-stage studies, results shown are from the combined analysis with all families when available …”
Section: Leprosymentioning
confidence: 99%
“…Moreover, chromosomal region 21q22 was linked to leprosy polarization in families from Malawi (Wallace et al 2004 ). Finally, 2p14 was significantly linked to leprosy per se, while regions 4q22, 8q24 and 16q24 showed suggestive evidence for linkage in Chinese families (Yang et al 2012 ). Leprosy susceptibility genes underlying these linkage peaks are yet to be identified.…”
Section: Leprosymentioning
confidence: 99%
“…A relatively small percentage of armadillos are resistant to M. leprae , and large sample sizes might be needed for conclusive genetic analysis. Genome-wide SNP linkage analysis and melting-curve-based assays have been used effectively to identify new SNPs in human studies (Misch et al, 2008; Yang et al, 2012), and the application of similar approaches might be possible with armadillos once the genome is fully annotated.…”
Section: Post-genomic Advancesmentioning
confidence: 99%